Modeling and simulation of modified skyhook controller for active suspension system - Muhamad Rusydi, Ali (2010)
The purpose of this project is to model and simulate the modified skyhook controller for active suspension system a for a quarter car model. There are four parts have beendeveloped in this study namely, the hydraulic actuator model, force tracking controller,quarter car for passive suspension system and modified skyhook for active suspensionsystem. The simulation process of this system was carried out using MATLAB andSIMULINK toolbox. The data for the each parameter were obtained from the research thathave done previously. Performance of active suspension system with modified skyhookcontroller is better than active suspension system with skyhook controller. The simulationresults show that the active suspension system could provide significant improvements inthe ride quality and road handling compare with the passive suspension system.